Microbiota of health, gingivitis, and initial periodontitis - Tanner, A.; Maiden, M. F. J.; Macuch, P. J.; Murray, L. L.; Kent Jr, R. L. (Journal of clinical periodontology, 1998)
. This study compared the subgingival microbiota in periodontal health, gingivitis and initial periodontitis using predominant culture and a DNA probe, checkerboard hybridization method. 56 healthy adult subjects with minimal periodontal attachment loss were clinically monitored at 3‐month intervals for 12 months. More sites demonstrated small increments of attachment loss than attachment gain over the monitoring period. Sites, from 17 subjects, showing ≥1.5 mm periodontal attachment loss during monitoring were sampled as active lesions for microbial analysis. Twelve subjects demonstrated interproximal lesions, and 5 subjects had attachment loss at buccal sites (recession). Cultural studies identified Bacteroides forsythus, Campylobacter rectus, and Selenomonas noxia as the predominant species associated with active interproximal lesions (9 subjects), whereas Actinomyces naeslundii, and Streptococcus oralis, were the dominant species colonizing buccal active sites. A. naesludii, Campylobacter gracilis, and B. forsythus (at lower levels than active sites) were the dominant species cultured from gingivitis (10 subjects). Health‐associated species (10 subjects) included Streptococcus oralis, A. naeslundii, and Actinomyces gerencseriae. DNA probe data identified higher mean levels of B. forsythus and C. rectus with active (7 subjects) compared to inactive periodontitis sites. Porphyromonas gingivalls and Actinobacillus actinomycetemcomitans were detected infrequently. Cluster analysis of the cultural microbiota grouped 8/9 active interproximal lesions in one subcluster characterized by a mostly gram‐negative microbiota, including B. forsythus and C. rectus. The data suggest that B. forsythus C. rectus and S. noxia were major species characterizing sites converting from periodontal health to disease. The differences in location and microbiota of interproximal and buccal active sites suggested that different mechanisms may be involved in increased attachment loss.